(untitled) (Journal of International English Research Studies (JIERS), ISSN: 3048-5231, 2023)
This comparative study delves into the multifaceted realm of multilingualism within the domain of English language education. With globalization and multiculturalism shaping modern societies, understanding the dynamics of multilingualism is crucial in educational settings. This research investigates various aspects of multilingualism, including its implications, challenges, and benefits, within the context of English language education across different socio-cultural landscapes. Drawing upon a mixed-methods approach, this study synthesizes quantitative data analysis with qualitative inquiry techniques. Quantitative analysis involves statistical examination of language proficiency levels, language acquisition patterns, and demographic variables among students. Qualitative inquiry comprises interviews, focus groups, and classroom observations to capture nuanced perspectives from educators, students, and administrators.